A study on the effectiveness of railway turnout by using roller cradle assembly along Kelana Jaya trackwork - Hassan Haszanizaam; Prasetijo Joewono (E3S Web of Conferences)
Malaysia's railway transportation industry has faced significant demand for increased train reliability. Railway turnouts are a specific track system used to divert train direction, which is a vital component for enabling rail operating flexibility. Passengers are directly affected by service disruptions, forcing them to wait or pick alternative public transportation options to get to their destination. This will lower service dependability and consumer satisfaction. This study was conducted to assess the primary failure connected to the permanent way subsystem, which is turnout operation. The aim of this study was to do statistical analysis on the turnout dry slide chair. The failure's major statistics were examined, as well as the right solution, the primary cause improvement, and the efficiency, which was proven by on-site testing. Normal practices were assessed to ensure their effectiveness and to identify any areas for permanent improvement. The proposed solution was evaluated to validate, compare, and determine the parameters that influence the solution's effectiveness. This rigorous testing result demonstrates that the underlying issue has been resolved, resulting in an instant friction reduction of 64% to 83% for depot turnouts, as well as better operational performance.